Study on the Characteristics and Influencing Factors of Selenium Content in Soil of Western Hubei Province, China - Qin, Haolin (International Journal of Natural Resources and Environmental Studies, 2024)
Mastering the distribution of selenium in soils is vital for the development of selenium-enriched industries. This study focuses on Xintang Township in Enshi City, western Hubei Province, known for its selenium-rich soils, analyzing 2,469 soil samples to understand selenium distribution and its influencing factors. Key findings include: 1. Selenium content in surface soils ranges from 0.14 to 25.74 mg/kg, with an average of 0.81 mg/kg, and 86.23% of the area has selenium-rich soils. 2. Soil selenium content is significantly influenced by the parent material, especially soils from the Permian black rock series, showing higher selenium levels with an enrichment factor of 3.74. 3. Soil type impacts selenium distribution, with yellow lime soil and brown lime soil showing high enrichment factors of 3.94 and 2.62, respectively.